Sertifikasi Produk Halal oleh BPJPH DIY dengan Pendekatan Ekonomi Politik Perspektif Maqasid Syariah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
This research aimed to observe how the model of halal certification of BPJPH DIY from maqasid syariah with the political-economic approach. This study is field research with the political-economic approach and consisted of four informants with data collection techniques through interview and documentation tracing. The data analysis included data condensation, data presentation, and conclusion. Based on the results of the research in the field, it was found that the model of halal certification by BPJPH DIY in the implementation of halal certification had a task to accept the registration and issue the halal certification. Meanwhile, the implementation of halal standardization still used the reference of SJH LPPOM MUI. The cost for halal certification for the category of SMEs will be the responsibility of the state. In addition, there were two posts of payment account: BPJPH and LPH (LPPOM). As seen from a political-economy approach, the existence of BPJPH has brought the interest of ideology, power, and economy. The business actors consider that BPJPH halal certification is in two-way form, both in the administrative process and certification cost. In the perspective of maqasid sharia, to secure the value of human life, society, and the environment is fulfilled; meanwhile, to secure human him/herself has not been fulfilled yet.